Chondrogenesis of bone marrow and peripheral blood derived adult human mesenchymal stem cells - Mansor, A.; Chong, Pan-Pan; Selvaratnam, L.; Nadarajah, V.S.; Sara, T.; Kamarul, Tunku (2008)
Although mesenchymal stem cells (MSCs) isolation from a number of tissue sources have been described, very few literatures have been reported successful isolation of adult MSCs from peripheral blood or its chondrogenic differentiation for clinical applications. The objective of this study is to isolate MSCs derived from both human bone marrow and peripheral blood and to compare their potential to undergo chondrogenesis.